The study of capacitance change during electrolyte penetration through carbon-supported hydrous ruthenium oxide prepared by the sol-gel procedure - Panić, V. V. (Array, 2009)
Summary: The changes in capacitive behavior of C/HxRuOy composite material prepared by impregnating the Vulcan® XC 72R carbon black with oxide sols of different particle size are investigated as the electrolyte penetrates through the thin layer of the Nafion®-covered composite. The techniques of cyclic voltammetry and electrochemical impedance spectroscopy are used. Results of the investigation reveal the influence of potential cycling and the exposure time to the electrolyte on registered capacitive characteristics of composite. The cycling in a wide potential range causes the decrease in energy storage ability which depends on oxide particle size. Impedance measurements, however, show that the ability initially decreases and subsequently increases during exposure to the electrolyte as the consequence of the presence of Nafion® top-layer. Due to wettability and resistance issues, Nafion® top-layer can affect the pseudo-capacitive characteristics, and the energy storage ability of the composite consequently decreases